A Walk in the Night with Zhuangzi : Musings on an Ancient Chinese Manuscript. - Huang, Kuan-yun. (Albany : State University of New York Press, 2023)
A complete translation and analysis of "All Things Flow into Form" (Fan wu liu xing), a recently discovered manuscript from the Warring States period (481-221 BCE).
Intro -- Contents -- Preface -- A Note on the Translation -- Part I. "All Things Flow into Form" -- "All Things Flow into Form": English Translation -- "All Things Flow into Form": Chinese Transcription -- Part II. Analysis -- 1 Solitude -- 2 Sincerity -- 3 "The Heart of Hearts" -- 4 Walking in the Night -- 5 One -- Concluding Remarks -- Acknowledgments -- Notes -- Index.
Description based on publisher supplied metadata and other sources.
JSTOR
Keywords: Fan wu liu xing; Philosophy, Chinese -- To 221 B.C.; Philosophie chinoise -- Jusqu'à 221 av. J.-C.; Philosophy, Chinese; To 221 B.C.